Port Mortuary - Cornwell, Patricia (United States : Sphere, 2010)
When Scarpetta examines a young man's body, she discovers stunning indications that he may have been alive when he was zipped inside a pouch and locked inside the cooler of her new Cambridge Forensic Center in Massachusetts. Various 3-D radiology scans reveal more shocking details about internal injuries unlike any Scarpetta has ever seen. These suggest the possibility of a conspiracy to cause mass casualties, and she races against time to discover who and why before more people die.
Keywords: Medical examiners (Law); Forensic pathologists; Women physicians; Terrorism -- Prevention; Legal stories